A Review Paper on Friction Stir Processing on Aluminium Alloys - Narender Kashyap; Sanjay Kumar; Shiv Narayan Prajapati (International Journal of Fracture Mechanics and Damage Science, 2024)
Friction stir processing is a step from friction stir welding, targeted at surface modification through improving the local microstructure via localized plastic deformation. The tool consists of a rotating mechanism incorporating a shoulder and pin that are inserted into the material, traversing the designated area. When the tool's shoulder and the workpiece make contact, friction develops, generating heat that produces plastic deformation. This localized plastic deformation and heat impact result in considerable modifications to the microstructure. Friction stir processing impacts various material properties, encompassing the formation of nanograins, increased surface hardness, improved fatigue strength, wear resistance, and tensile strength. This study predominantly explores the alterations observed in the microstructure and mechanical attributes of aluminium alloys and their composites through friction stir processing, examining the present trends and advancements in process parameters.
Keywords: CBP; FSW; Friction stir processing; XRD; scanning electron microscopy